Evaluating teaching factory implementation in vocational centers of excellence using the CIPP model: a mixed-methods study - Safrinanda Harahap; Fahmi Rizal; Faisal Ashar; Yuliana Yuliana; Liana Atika; Wisnu Prayogo (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study evaluated the Teaching Factory program in three Vocational Centers of Excellence in Binjai City, Indonesia, using the Context, Input, Process, and Product (CIPP) model. A sequential explanatory mixed-methods design combined questionnaire data from the total population of 9 teachers and 128 students, selected through purposive sampling, with interviews, observation, and documentation. Achievement scores were positive for both groups on Context (teachers 82.4%, students 84.6%), Process (83.2%, 77.4%), and Product (81.1%, 79.9%). The clearest divergence emerged on Input: teachers rated resource readiness positively (83.3%), while students rated it the weakest component (69.0%), indicating a gap between policy-level resourcing and field-level experience, particularly in equipment standardization and facility capacity. Qualitative findings converged with this pattern, confirming all three schools remained at an early, competency-fulfilment stage rather than a market-oriented production stage. The program is feasible to continue, provided industrial partnership, input governance, and facility investment are strengthened.